Does anyone survive pancreatic ductal adenocarcinoma? A nationwide study re-evaluating the data of the Finnish Cancer Registry. (11th February 2005) - Carpelan-Holmström, M; Nordling, S; Pukkala, E; Sankila, R; Lüttges, J; Klöppel, G; Haglund, C
Abstract : Background: Worldwide survival data for ductal adenocarcinoma of the pancreas are the lowest among the 60 most frequent types of organ cancers. Hence published data on long time survivors of this disease are controversial. We performed a nationwide study comprising all Finnish patients diagnosed with pancreatic cancer in the period 1990–1996 who survived for at least five years after diagnosis. Methods: Data on patients registered as five year survivors of pancreatic cancer were obtained from the Finnish Cancer Registry and Statistics Finland. Slides or paraffin blocks were collected from patients recorded as having histologically proven pancreatic ductal adenocarcinoma (PDAC) and were re-evaluated in a double blind fashion by three pathologists with special expertise in pancreatic pathology. Results: Between 1990 and 1996, the Finnish Cancer Registry recorded 4922 pancreatic cancer patients, 89 of whom survived for at least five years. Reviewing this series of patients revealed 45 (49%) non-PDACs and 18 cases without histological verification. In 26 patients recorded as having histologically proven PDAC, re-evaluation of histological specimens confirmed PDAC in only 10 patients. Conclusions: This study indicates that (1) the prognosis of PDAC remains poor and (2) careful histopathological review of all patients with pancreatic cancer is mandatory if survival data are to be meaningful.